A Case Study of Chinese Children's Biliteracy Learning at Home and School - Xiaoxiao Du (Canadian Society for Studies in Education, 2016)
Canada is a multicultural and multilingual country with a large number of immigrants. It is therefore not unusual to see a highly diverse student population in Canadian elementary schools. This study examined primary grade Chinese immigrant children's biliteracy learning at home using a qualitative case study approach. Data collection included home visits, interviews with parents, and conversations with children. Interpretational analysis was used when analyzing data (observational notes, interview transcriptions, and research journals) in order to identify emerging themes of biliteracy learning at home. The findings of my study indicate that several factors might affect children's biliteracy learning at home including parents' education background, attitudes, motivations, expectation level, degree of support toward biliteracy, as well as literacy resources and language environment. This study may help educators further understand Chinese children's literacy learning at home and could encourage parents to more actively support their children's biliteracy learning.